Quantitative relationship between grip strength and quality of life in the older adult based on a restricted cubic spline model - Fanhao Meng; Yunqing Zhang; Yunqing Zhang; Chaoxing Liu; Chaoxing Liu; Cailiang Zhou (Frontiers Media S.A., 2024)
BackgroundGrip strength have been showed diverse associations with quality of life for the older adult population in the literature, still there is lack of evidence of the threshold value of grip strength for maintaining good quality of life in older adults. The purpose of this study was to study the dose-effect relationship between grip strength and quality of life in the older adult, and to explore the factors affecting quality of life in the older adult, so as to provide effective theoretical basis for realizing healthy aging.MethodsA total of 105 older adult people over 60 years old were selected from 3 communities in Beijing. Grip strength was measured by hand dynamometer apparatus and quality of life was assessed by 36-item Short-Form (SF-36). On the basis of controlling confounding factors, the dose-effect relationship between grip strength and quality of life was analyzed with the restricted cubic spline model.ResultsThe results showed that there was a dose-effect relationship between grip strength and physical component summary (PCS) (p < 0.01). However, grip strength was not significantly associated with mental component summary (MCS) (p > 0.05). The threshold value of grip strength for male and female is 34.75 and 23.2 kg, for normal weight group and overweight and obesity group is 24.82 and 29.00 kg, for 60-69, 70-79, 80+ years group is 24.88, 23.37, and 22.97 kg, respectively. When the grip strength value is lower than the threshold value, the increase of grip strength was related to significant improvement of quality of life of the older adult, and when the grip strength value is higher than the threshold value, the quality of life can be maintained in good condition.ConclusionA dose-effect relationship was found between grip strength and physical health in quality of life. Results of our study indicated that the grip strength of the older adults needed to be greater than certain threshold values to maintain good quality of life.